Brain volume and perfusion asymmetry in temporal lobe epilepsy with and without hippocampal sclerosis. (3rd April 2021) - Zhang, Yiwei; Dou, Wanchen; Zuo, Zhentao; You, Hui; Lv, Yuelei; Hou, Bo; Shi, Lin; Feng, Feng
ABSTRACT: Objectives : To detect and compare the features of interictal perfusion and volume asymmetry between temporal lobe epilepsy (TLE) patients with and without hippocampal sclerosis (HS). Methods : Sixty-one TLE patients (mean age 28.4 ± 9.3 years; 28 female/33 male) with unilateral signs of HS (TLE-HS+) and 25 TLE patients (mean age 29.8 ± 8.0 years; 17 female/8 male) without HS (TLE-HS-) were included. Thirty healthy volunteers served as controls (mean age 26.0 ± 8.7 years; 22 female/8 male). Brain segmentation and volume calculation were performed. Quantitative cerebral blood flow (CBF) values were measured based on arterial spin labeling (ASL). The asymmetry indices (AIs) of volume and perfusion were calculated. Results : TLE-HS+ (adjusted P = 0.001) and TLE-HS- patients (adjusted P = 0.006) had significantly higher hippocampal perfusion AIs than controls. TLE-HS+ and TLE-HS- had similar hippocampal perfusion AIs (adjusted P = 1.00). TLE-HS+ had higher hippocampal volume AIs than TLE-HS- and controls (adjusted P < 0.001). TLE-HS- and controls had similar hippocampal volume AIs (adjusted P = 1.00). All (100%) TLE-HS+ patients had positive hippocampal perfusion or volume AIs. No significant correlation between the AIs of hippocampal perfusion and volume was found in both TLE-HS+( P = 0.894) and TLE-HS- ( P = 0.106) patients. TLE-HS+ patients demonstrated more extensive whole-brain asymmetry of both perfusion and volume than TLE-HS- patients. Conclusion : TLE-HS+ and TLE-HS- patients have different patterns of whole-brain perfusion and volume asymmetry. Hippocampal perfusion asymmetry was revealed in both TLE-HS+ and TLE-HS- patients.